Kuwait : 2010 Article IV Consultation; Staff Report and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2010)
Kuwait's economy was affected significantly by the global crisis. The financial sector experienced funding pressures and deterioration in asset quality. The economic outcome depends largely on government spending and the associated private investment. Stress tests indicate that the banking system can withstand shocks. The macroeconomic policy mix is adequate, but growth of current expenditures should be contained. Successful implementation of the growth agenda requires progress in structural reforms. The financial system's oversight framework should be strengthened. The household debt relief law can undermine the financial culture.